2014
DOI: 10.1039/c4cp01582g
|View full text |Cite
|
Sign up to set email alerts
|

Conversion efficiency of skutterudite-based thermoelectric modules

Abstract: Presently, the only commercially available power generating thermoelectric (TE) modules are based on bismuth telluride (Bi2Te3) alloys and are limited to a hot side temperature of 250 °C due to the melting point of the solder interconnects and/or generally poor power generation performance above this point. For the purposes of demonstrating a TE generator or TEG with higher temperature capability, we selected skutterudite based materials to carry forward with module fabrication because these materials have ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
95
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 25 publications
4
95
0
1
Order By: Relevance
“…Cook et al reported 20% conversion efficiency for a 3-stage TEG that utilized HH alloys in the high temperature stage [5]. These reported TEG efficiencies are already higher than those of state-of-the-art TEGs [11][12][13][14]. The power density output of HH alloy based TEG was reported to exceed 3 W/cm 2 [3].…”
mentioning
confidence: 99%
“…Cook et al reported 20% conversion efficiency for a 3-stage TEG that utilized HH alloys in the high temperature stage [5]. These reported TEG efficiencies are already higher than those of state-of-the-art TEGs [11][12][13][14]. The power density output of HH alloy based TEG was reported to exceed 3 W/cm 2 [3].…”
mentioning
confidence: 99%
“…Therefore, other above-listed materials with less toxicity have recently been utilized for TE modules. [6][7][8] They are expected to be put into practical use in the near future if the cost performance is more improved.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Skutterudite antimonide is one of the most promising candidates for intermediate temperature TE power generation (500-900 K) owing to the availability of both high-performance n-and p-type compositions within this material class with excellent thermomechanical properties and relatively low-cost and abundant constituent elements (compared with the state-of-the-art Bi 2 Te 3 and PbTe). [4][5][6][7][8][9] Guest filling in the structural nanovoids to form the so-called filled skutterudites (i.e., R y (Co,Fe) 4 Sb 12 , where R represents the filler and y the filling fraction) is the best strategy for enhancing the TE figure of merit ZT as the fillers both act to control carrier concentration and significantly suppress the propagation of heat-carrying phonons. 6,7 Many elements can be partially filled in CoSb 3 , such as alkali, alkaline earth, rare earth, and group IIIA elements.…”
Section: Introductionmentioning
confidence: 99%